Karakteristik Morfologi Jenis-Jenis Tanaman Obat Di Kelurahan Prabujaya Kecamatan Prabumulih Timur Kota Prabumulih - Dia Nita Utami; Dewi Rosanti; Trimin Kartika (Indobiosains, 2023)
Research that examines the morphological characteristics of medicinal plants in Prabujaya Village, Prabumulih City has been carried out from April 2022 to May 2022. This study uses a survey method. Direct retrieval explores the area of ​​Prabujaya Village, East Prabumulih District, Prabumulih City. Sampling was done by direct observation, by looking at the list of Indonesian medicinal plants and the results of direct interviews with the community. The results of the study found that there were medicinal plants from the Spermatophyta divisio, consisting of 2 classes, 12 orders, 12 families, 18 genera and 18 species. The root morphology type (Radix) has taproot and fibrous root. The stem morphology (Caulis) is in the form of pseudo stem, woody stem, wet stem and grass stem. Leaf morphology (Folium) is lanceolate (lanceolatus), elongated (oblongus), ovoid (ovatus), ribbon (ligulatus) and oblong (ovalis). Flower morphology (FLOs) includes single interest, compound interest bunches, compound interest, grain compound interest, pseudo compound interest, umbrella compound interest, strand compound interest. Fruit morphology (Fructus) includes true fruit types of buni fruit, citrus fruit, kendaga fruit, compound stone fruit, dry single true fruit, compound true fruit, and pseudo true fruit. The parts of the organs used as medicine are leaves, rhizomes, roots, stems, flowers, and fruit.